HIV infection and engagement in HIV care cascade among men who have sex with men and transgender women in Kigali, Rwanda: a cross‐sectional study. (1st October 2020) - Twahirwa Rwema, Jean Olivier; Lyons, Carrie E; Herbst, Sara; Liestman, Benjamin; Nyombayire, Julien; Ketende, Sosthenes; Mazzei, Amelia; Olawore, Oluwasolape; Nsanzimana, Sabin; Mugwaneza, Placidie; Kagaba, Aflodis; Sullivan, Patrick S; et al.
Abstract: Introduction: Given intersecting biological, network and structural risks, men who have sex with men (MSM) and transgender women (TGW) consistently have a high burden of HIV. Although MSM are a key population in Rwanda, there are limited epidemiologic data to guide programming. This study aimed to characterize HIV prevalence and care cascade among MSM and TGW in Kigali. Methods: MSM and TGW ≥ 18 years were recruited using respondent‐driven sampling (RDS) from March–August 2018 in Kigali. Participants underwent a structured interview including measures of individual, network and structural determinants. HIV and sexually transmitted infections (STI) including syphilis, Neisseria gonorrhoea (NG) and Chlamydia trachomatis (CT) were tested. Viral load was measured for MSM living with HIV. Robust Poisson regression was used to characterize the determinants of HIV infection and engagement in the HIV treatment cascade. Results: A total of 736 participants were enrolled. The mean age was 27 years (range:18 to 68) and 14% (106) were TGW. HIV prevalence was 10% (RDS‐adjusted: 9.2% (95% CI: 6.4 to 12.1)). Unadjusted prevalence of any STI was 20% (147); syphilis: 5.7% (42); CT: 9.1% (67) and NG: 8.8% (65). Anticipated (41%), perceived (36%) and enacted stigmas (45%) were common and higher among TGW ( p < 0.001). In multivariable RDS adjusted analysis, higher age (aPR: 1.08 (95% CI: 1.05 to 1.12)) and ever having sex with women (aPR: 3.39 (95% CI: 1.31 to 8.72)) were positively associated with prevalent HIV. Being circumcised (aPR: 0.52 (95% CI: 0.28 to 0.9)) was negatively associated with prevalent HIV infection. Overall, 61% (45/74) of respondents reported knowing their HIV‐positive status. Among these, 98% (44/45) reported antiretroviral therapy use (ART); 75% (33/44) were virally suppressed using a cut‐off of <200 copies/mL. Of the 29 participants who did not report any previous HIV diagnosis or ART use, 38% (11/29) were virally suppressed. Cumulatively, 59% (44/74) of all participants living with HIV were virally suppressed. Conclusions: These data show a high burden of HIV among MSM/TGW in Kigali, Rwanda. Bisexual concurrency was common and associated with prevalent HIV infection, demonstrating the need of comprehensive screening for all sexual practices and preferences in the provision of comprehensive HIV prevention services in Rwanda. Viral suppression was below the UNAIDS target suggesting poor adherence and potential ART resistance. There is a need for adherence support, screening for primary and secondary ART resistance and stigma mitigation interventions to optimize HIV‐related outcomes for MSM in Rwanda.